USE OF PRODUCTS OF HEMP SEED PROCESSING IN THE PRODUCTION OF BREAD - BLAZHENKO, MARIIA; FALENDYSH, NATALIIA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The consumption of bread and bakery products made from wheat flour is one of the integral parts of the diet of both Ukrainians and other peoples of the world, due to its relatively low cost, but high calorie content. However, today there is a trend in society towards development and transition to a healthy and balanced diet. Changing the philosophy of food consumption is not only to satisfy hunger, but also to improve health and close the need for micro- and macronutrients for the normal functioning of the human body. In recent years, manufacturers of the bakery industry have paid special attention to the expansion of the range of bread and bakery products with increased nutritional and biological value due to the use of non-traditional raw materials. In particular, extracts of plant medicinal herbs, meal from oil crops, bran of cereal crops, flour and protein from crops with an increased content of micro- and macroelements in their chemical composition are relevant raw materials for enriching bread and bakery products. Hemp seed processing products are promising raw materials for expanding the range of bread and bakery products with increased nutritional and biological value due to their qualitative and quantitative chemical composition. Thus, a study of the influence of the use of hemp protein and kernels on the change in the properties of the dough, the course of the technological process and the quality of finished products in the production of bread from wheat flour of the first grade was carried out. A comparison of the quality indicators of the control and experimental samples with the replacement of wheat flour with hemp protein 10, 15 and 20% and the additional introduction of hemp seed kernels 10, 15 and 20% was performed. It has been established that replacing 10 to 20% of first-grade wheat flour with hemp protein and adding a similar amount of hemp kernels contributes to the intensification of the dough ripening process and the reduction of the duration of the technological process by 8-20 minutes. Replacing wheat flour with hemp protein in the amount of 10 and 15% makes it possible to obtain bread that, according to organoleptic and physicochemical indicators, is not significantly inferior to the control sample.
Keywords: bread; bakery products; hemp seeds; hemp protein